Microbial community shifts in a farm-scale anaerobic digester treating swine waste: Correlations between bacteria communities associated with hydrogenotrophic methanogens and environmental conditions - Cho, Kyungjin; Shin, Seung Gu; Kim, Woong; Lee, Joonyeob; Lee, Changsoo; Hwang, Seokhwan (Elsevier BV, 2017)
Microbial community structure in a farm-scale anaerobic digester treating swine manure was investigated during three process events: 1) prolonged starvation, and changes of 2) operating temperature (between meso-and thermophilic) and 3) hydraulic retention time (HRT). Except during the initial period, the digester was dominated by hydrogenotrophic methanogens (HMs). The bacterial community structure significantly shifted with operating temperature and HRT but not with long-termstarvation. Clostridiales (26.5-54.4%) and Bacteroidales (2.513.7%) became dominant orders in the digester during the period of HMdominance. Abundance of diverse meso-and thermophilic bacteria increased during the same period; many of these species may be H-2 producers, and/or syntrophic acetate oxidizers. Some of these species showed positive correlations with [NH4+-N] (p < 0.1); this relationship suggests that ammonia was a significant parameter for bacterial selection. The bacterial niche information reported in this study can be useful to understand the ecophysiology of anaerobic digesters treating swine manure that contains high ammonia content. (C) 2017 Elsevier B.V. All rights reserved.